Use of a titanium device in lateral sinus floor elevation: an experimental study in monkeys - Schweikert, Michael; Botticelli, Daniele [UNESP]; Oliveira, José Américo de [UNESP]; Scala, Alessandro [UNESP]; Salata, Luiz A.; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Aim: To evaluate the effect of a space-maintaining device fixed to the lateral wall of the maxillary sinus after the elevation of the sinus mucosa on bone filling of the sinus cavity. Material and methods: Immediately after the elevation of the maxillary sinus Schneiderian membrane accomplished through lateral antrostomy in four monkeys, a titanium device was affixed to the lateral sinus wall protruding into the sinus cavity to maintain the mucosa elevated without the use of grafting material. The healing of the tissue around the implants was evaluated after 3 and 6 months. Ground sections were prepared and analyzed histologically. Results: The void under the elevated sinus membrane, originally filled with the blood clot, was reduced after 3 as well as after 6 months of healing of about 56% and 40.5%, respectively. In seven out of eight cases, the devices had perforated the sinus mucosa. The formation of mineralized bone and bone marrow amounted to about 42% and 69% after 3 and 6 months, respectively. The connective tissue represented about 53% and 23% of the newly formed tissue after 3 and 6 months, respectively. Conclusions: New bone formation was found below the devices. However, shrinkage of the newly formed tissue was observed both after 3 and 6 months of healing. Hence, the space-maintaining function of the devices used in the present study has to be questioned.
Keywords: animal study; bone formation; lateral approach; osseointegration; sinus floor elevation; titanium device